Effects of Waterpipe Tobacco Smoking on the Spirometric Profile of University Students in Palestine: A Cross-Sectional Study - Zaher Nazzal; Deema Odeh; Fatima Azahraa Haddad; Mohammad Berawi; Belal Rahhal; Hasan Yamin (Canadian Respiratory Journal)
Background. Waterpipe smoking in young individuals is increasing with limited studies addressing its respiratory health effects. The aim of the study was to determine the effect of waterpipe smoking on young adults’ lung functions. Spirometric parameters were compared between waterpipe smokers and nonsmokers. Methods. A comparative cross-sectional study of university students, including males and females, was conducted. An interviewer-administered questionnaire was used to record students’ characteristics. The spirometry test was performed to assess students’ lung functions; we recorded the forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), FEV1/FVC ratio, peak expiratory flow (PEF), and forced expiratory flow between 25 and 75% of FVC (FEF25–75%). Results. A total of 300 apparently healthy students (150 waterpipe smokers and 150 nonsmokers) were included in the study. Waterpipe smokers showed significantly lower values in FEV1, FEV1/FVC ratio, PEF, and FEF25–75% compared to the nonsmoker group (P<0.05 to P<0.001). The subgroup analysis on female students (50 WP smokers and 50 nonsmokers) showed a significant decrease in FEV1/FVC ratio, PEF, and FEF25–75% parameters (P<0.001). Conclusion. Waterpipe smoking is associated with reduced spirometric parameters in healthy young adults with relatively limited smoking years.